HybPhaser: A workflow for the detection and phasing of hybrids in target capture data sets. (21st July 2021) - Nauheimer, Lars; Weigner, Nicholas; Joyce, Elizabeth; Crayn, Darren; Clarke, Charles; Nargar, Katharina
Abstract : PREMISE: Hybrids contain divergent alleles that can confound phylogenetic analyses but can provide insights into reticulated evolution when identified and phased. We developed a workflow to detect hybrids in target capture data sets and phase reads into parental lineages using a similarity and phylogenetic framework. METHODS: We used Angiosperms353 target capture data for Nepenthes, including known hybrids to test the novel workflow. Reference mapping was used to assess heterozygous sites across the data set and to detect hybrid accessions and paralogous genes. Hybrid samples were phased by mapping reads to multiple references and sorting reads according to similarity. Phased accessions were included in the phylogenetic framework. RESULTS: All known Nepenthes hybrids and nine additional samples had high levels of heterozygous sites, had reads associated with multiple divergent clades, and were phased into accessions resembling divergent haplotypes. Phylogenetic analysis including phased accessions increased clade support and confirmed parental lineages of hybrids. DISCUSSION: HybPhaser provides a novel approach to detect and phase hybrids in target capture data sets, which can provide insights into reticulations by revealing origins of hybrids and reduce conflicting signal, leading to more robust phylogenetic analyses.